Soil Application of Wheat Straw Vermicompost Enhances Morpho-Physiological Attributes and Antioxidant Defense in Wheat Under Drought Stress - Ahmad, Ali; Aslam, Zubair; Hussain, Saddam; Javed, Talha; Hussain, Sadam; Bashir, Safdar; Hussain, Iqtidar; Belliturk, Korkmaz; Adamski, Robert; Siuta, Dorota; Dessoky, Eldessoky S.; Hessini, Kamel (Frontiers in Environmental Science, 2022)
With the provoked environmental constraints under extreme climatic events, a better understanding of plant responses to these environmental stresses helps in obtaining sustainable productivity. Wheat is a significant cereal crop for the burgeoning population; its yield is significantly limited by too little water in the rhizosphere. The ramifications of water deficiency on the wheat crop can be reduced by the application of vermicompost. With the objective to cope with drought stress, a wire-house experiment was established where seedlings of two cultivars, viz., Faisalabad-08 and Galaxy-13 (drought-tolerant and -sensitive cultivar, respectively) were grown in pots and exposed to mild drought (D1, 45% field capacity) and severe drought stress (D2, 30% field capacity). A control with well-watered condition (70% field capacity) was kept for comparison. Various application rates of wheat straw vermicompost (control (VT0), 4 t ha−1 (VT1), 6 t ha−1 (VT2), and 8 t ha−1 (VT3)), were used in soil-filled pots under drought and control treatments. Our data depicted that compared with control, drought treatments recorded a significant reduction in morpho-physiological and biochemical attributes with maximum reduction under severe drought conditions. Nonetheless, it was observed that soil application of vermicompost, particularly at a high rate, ameliorated the negative effects of drought. Under severe drought conditions, a significant and positive influence on morphological and physiological traits was recorded for VT3 treatment, which increased root and shoot length by 27.55 and 27.85%, root and shoot fresh weight by 26.98 and 28.20%, root and shoot dry weight by 40 and 50.05%, and photosynthesis and transpiration rate by 27.65 and 49.25%, respectively, on average of two cultivars. Similarly, VT3 also significantly ameliorated the adverse effect of drought by enhancing the antioxidant enzyme activities as it increased superoxide dismutase activity by 14.28%, peroxidase by 27.28%, and catalase by 50% compared to the control treatment. Among cultivars, Faisalabad-2008 showed comparatively more resistance against drought stress. The findings of this work revealed that drought drastically reduced the growth and productivity of wheat; however, soil-applied vermicompost positively influenced the performance of wheat cultivars.